Cloud Computing Adoption and Academic Performance in Higher Education: An Extended Technology Acceptance Model Approach - Jamali, Syed; Laxman, Kumar; Nidarsha Silva, Inasi Rangana (Innovations in Pedagogy and Technology, 2026)
While cloud computing has become more widespread in higher education, research examining its adoption through integrated theoretical models remains limited, especially in developed, small-market settings like New Zealand (NZ). Existing studies often rely on core Technology Acceptance Model (TAM) constructs and mainly focus on adoption intentions, with little attention to cloud-specific features and academic performance outcomes. To address these gaps, this study develops and tests an extended TAM model that includes key cloud computing characteristics such as security, cost efficiency, scalability, and accessibility, and explores their relationship with students’ academic performance. Using survey data from tertiary students in New Zealand, the model is empirically tested with quantitative analysis methods. The findings show that perceived usefulness and ease of use significantly influence cloud computing adoption, and cloud-specific features further reinforce adoption behaviour. Importantly, the results also reveal a positive link between cloud computing adoption and students’ academic performance. This study advances theory by extending TAM to include context-specific technological attributes and outcome variables, and offers practical insights for higher education institutions aiming to improve learning results through effective cloud technology deployment. Ultimately, by enhancing the integration and efficiency of cloud technology in academic settings, educational institutions and technology providers can better meet the needs and preferences of students and instructors by understanding and addressing these concerns.